The Role of Functional Foods in Chronic Disease Prevention: A Clinical Trial Investigating Nutritional Interventions in Type 2 Diabetes Management - Muhammad Sajjad; Huma Arooj Tahir; Al Ayesha Farooq; Areeja Nasir; Faziyya Latif; Faryal Gohar; Usman Iftikhar (Research Journal of Psychology, 2025)
Background: Type 2 Diabetes (T2DM) is a metabolic disease due to insulin resistance associated with chronic inflammation. While pharmacological treatment remains primary, functional foods rich in bioactive substances such as polyphenols, omega-3 fatty acids, probiotics, and fiber show promise for improving glycemic control and metabolic health Objective: This study aimed to assess the impact of the supplementation of functional foods on glycemic control, lipid metabolism, inflammatory markers, gut microbiota, and body composition among people with type 2 diabetes (T2DM) Methodology: 150 participants completed a 12-week randomized, double-blind, placebo-controlled intervention. The participants contained functional foods in the intervention group while the placebo was comprised of a biologically inactive substitute. Assessment of key metabolic parameters was done before and after the intervention. Results: The intervention showed significant improvements in fasting blood glucose (168.4 ± 25.7 mg/dL to 144.2 ± 19.5 mg/dL, p < 0.001) and HbA1c (8.3% ± 0.6% to 7.4% ± 0.5%, p < 0.001). The lipid profiles and inflammatory markers also improved (p < 0.05). While there was a decrease in body fat percentage, there was a favorable structural shift in gut microbiota. Conclusion: It has been seen that functional foods play a key role in metabolic health improvements in T2DM patients, thus creating support for their use as an effective non-pharmacological approach to diabetes management. Future studies should aim to determine the long-term efficacy and applicability of individualized applications.